Prospective Mathematics Teacher Students’ Experiences in Visual Programming: Difficulties and Obstacles in Designing Digital Media for Numeracy Learning - Lestariningsih, Lestariningsih; Fareza, Mohamad Zulfahmi Al (FKIP Universitas Lampung, 2024)
Prospective mathematics teacher students' lack of understanding of basic math concepts, such as numeracy, is one of the main challenges in learning. In the era of rapid technological development, they must adapt, one of which is through visual programming to strengthen their numeracy. However, they often face difficulties and obstacles in the learning process of visual programming, both from technical and non-technical aspects. This research aims to analyze the difficulties and obstacles of prospective mathematics teacher students in learning visual programming. The research used the Colaizzi method to analyze qualitative data, which was then combined with clustering techniques to group the problems into five main clusters. The results show that the main difficulties are programming related knowledge (syntax/rules for writing code, determining variables, concepts and principles, functions and parameters, define code structure and loops, apply in numeracy/mathematics concept), skills in programming, understanding of program semantics (code), debugging, lack of practice. In addition, the obstacles faced by prospective mathematics teacher students are a lack of skills and understanding of basic programming concepts, such as code structure, syntax, and debugging, as well as the application of concepts to the context of numeracy/mathematics. In addition, there are internal barriers in the form of negative perceptions, dislike for programming, and low motivation to learn. This problem is exacerbated by the heavy course load, such as learning many topics quickly and teaching methods that are less structured and do not support effective learning. These difficulties and obstacles need to be addressed through more targeted and innovative learning approaches, such as integrating technology that supports a basic understanding of programming and training that builds motivation and changes negative perceptions towards visual programming. Keywords: visual programming, difficulties, obstacles, digital media, numeracy. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1678-1692